2022
DOI: 10.1002/ps.7077
|View full text |Cite
|
Sign up to set email alerts
|

New insights into cypermethrin insecticide resistance mechanisms of Culex pipiens pallens by proteome analysis

Abstract: BACKGROUND: Due to the development of insecticide resistance in mosquitoes, with worldwide mosquito-borne diseases resurgence in recent years, recent advances in proteome technology have facilitated a proteome-wide analysis of insecticide resistance-associated proteins in mosquitoes. Understanding the complexity of the molecular basis of insecticide resistance mechanisms employed by mosquitoes will help in designing the most effective and sustainable mosquito control methods. RESULTS: After 30 generations, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Other studies showed that chitin synthase or larval/pupal cuticular protein had higher transcript level in pyrethroid resistant bed bug strains (Mamidala et al, 2012; Koganemaru et al, 2013). In particular, the larval cuticle protein A3A has also been detected among up-regulated transcripts in resistant insects (Gao et al, 2018; Zhang et al, 2022), including bed bugs (see Supplementary table 6 in Mamidala et al 2012) . Interestingly, two A3A proteins detected as up-regulated in London Field strain were overlapping with a putative inverted duplication (Haberkorn et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that chitin synthase or larval/pupal cuticular protein had higher transcript level in pyrethroid resistant bed bug strains (Mamidala et al, 2012; Koganemaru et al, 2013). In particular, the larval cuticle protein A3A has also been detected among up-regulated transcripts in resistant insects (Gao et al, 2018; Zhang et al, 2022), including bed bugs (see Supplementary table 6 in Mamidala et al 2012) . Interestingly, two A3A proteins detected as up-regulated in London Field strain were overlapping with a putative inverted duplication (Haberkorn et al, 2023).…”
Section: Discussionmentioning
confidence: 99%